A Translation Analysis Of Interrogative Sentences In Subtitling Of The social Network Movie - IFTITAH, ANISA LATIF (2012)
This research studies the interrogative sentences in the Social Network movie. The objectives of the study are to identify the types of interrogative sentences found in the Social Network movie and to describe the equivalence of interrogative sentences found in the Social Network movie and its subtitle. This research is a descriptive qualitative research. The data are in the form of sentences containing interrogative sentence. The data source is the Social Network movie. The data are analyzed by using comparing method. The results of the research show that firstly, there are three types of interrogative sentences, namely; yes-no questions, tag questions, and interrogative-word questions. From 177 data, there are 83 or 47% data belong to yes-no questions (31 or 17,5% data of yes-no questions with tense auxiliary, 41 or 23,2% data of yes-no questions with do auxiliary, and 11 or 6,3% data of yes-no questions with modal auxiliary), 92 or 52% data belong to interrogative-word questions (7 or 4% data of who, 48 or 27,1% data of what, 6 or 3,4% data of when, 3 or 1,7% data of where, 16 or 9% data of why, and 12 or 6,8% data of how), and , 2 or 1% data belong to tag questions. These percentages show that interrogative-word question is the most dominant. It is so, because the speakers in the movie want to get more information. Secondly, the equivalence of the data is devided into two, they are; equivalent subtitle and non-equivalent subtitle. From 177 analyzed data, there are 159 or 90% equivalent subtitles and 18 or 10% nonequivalent subtitle. From these percentages, it can be concluded that the translation of interrogative sentences found in the Social Network movie into its subtitle is an equivalent translation.